GUIDED SYNCRETISM: REPACKAGING BADAGRY-OGU MUSIC IN THE CONTEXT OF LAGOS' POSTCOLONIAL MODERNITY - Kunnuji, Joseph (International Library of African Music, 2017)
At the Congress of Berlin (1884—85), the colonial governments created and imposed boundaries on the people of the continent, thereby fragmenting, for example, Gbe ethnolinguistic groups into different west-African countries, under the administrations of Britain, France and Germany. The Badagry-Ogu ethnic group, being the only Gbe ethnolinguistic group in Nigeria, which was colonised by the British government, was marginalized due to its positionality. Badagry-Ogu musical practices experienced the same situation and they have consistently waned over the years. These days, due to the effects of a postcolonial modernity in Lagos the indigenous is perceived as inferior, resulting in the condescending attitude of Badagry-Ogu youth towards their heritage. This paper describes the process of creating an experimental musical style, which syncretises Badagry-Ogu music and American jazz. This process involves the collection of music, engagement with performers, analysis and arranging of music and music making, with the thought of revitalising the interest of the youth trained in western music to engage more with their heritage, while making Ogu music more widely accessible in the global context. Supporting the argument for composition as a living archive, this paper features a new approach to musical conservation in Badagry Lagos.
Keywords: Jazz; Gun (African people); Postcolonialism; Guided Syncretism; Modernity; Repackaging; Hybridity; Postcolonial Studies; Nigeria; Badagry-Ogu; African Music